2017
DOI: 10.1038/s41598-017-16133-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient near infrared light emitting electrochemical cell (NIR-LEEC) based on new binuclear ruthenium phenanthroimidazole exhibiting desired charge carrier dynamics

Abstract: Near-infrared light-emitting electrochemical cell (NIR-LEEC) has emerged as a new and promising lighting sourcewhich could serve as low-cost alternatives in NIR light-emitting sources which are typically expensive. LECs were also shown advantages such as light weight, simplicity and low operation voltages. However, only a few examples of NIR-LEEC are reported in which external quantum efficiency(EQE) of devices limited to 0.1%. Here, we report, efficient NIR-LEEC based of two novel binuclear ruthenium phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, for several applications a high-frequency power supply is not practical. In this context, it is important that Bideh and Shahroosvand were able to record a luminance of 742 cd/m 2 at 690 nm at a constant current density of 222.4 mA/cm 2 from an LEC using a Ru-complex as the emitter; unfortunately, the operational lifetime was short at <20 min. Our group recently reported an LEC comprising a metal-free alternating copolymer as the emitter, which delivered stable NIR emission at 129 μW/cm 2 and 705 nm when driven by a constant current density of 74.5 mA/cm 2 …”
Section: Introductionmentioning
confidence: 99%
“…However, for several applications a high-frequency power supply is not practical. In this context, it is important that Bideh and Shahroosvand were able to record a luminance of 742 cd/m 2 at 690 nm at a constant current density of 222.4 mA/cm 2 from an LEC using a Ru-complex as the emitter; unfortunately, the operational lifetime was short at <20 min. Our group recently reported an LEC comprising a metal-free alternating copolymer as the emitter, which delivered stable NIR emission at 129 μW/cm 2 and 705 nm when driven by a constant current density of 74.5 mA/cm 2 …”
Section: Introductionmentioning
confidence: 99%
“…reported sterically hindered complexes 10, 11a, 11b and 12 (Fig. 6), by systematically adding methyl groups on the bpy ligand(s) [from zero (10) to two (11a and 11b) and to four (12)]. [50] All complexes were obtained as racemic mixtures, with the Λ as the major isomer, except for the most hindered 12, which was obtained as the single Λ-isomer.…”
Section: Rumentioning
confidence: 99%
“…1 V and three reduction peaks (the first two reversible and the last one quasi-reversible), corresponding to each of the bpy ligands. In addition, the versatility of Ru(II) polypyridyl complexes as energy donors, electron acceptors and electron donors along with their great stability in solution, tunability and ease of synthesis [1] make them excellent candidates as catalysts, [2][3][4] solar dyes, [5][6][7] in light-emitting electrochemical cells [8][9][10] and light-emitting diodes, [11] as well as in many biological applications such as anticancer agents [11][12][13][14][15] or photosensitizers for photodynamic therapy (PDT). [16][17][18][19][20] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This work is notably justified by the fact that LECs based on complexes comprising phenanthroimidazole ligands often lack the acceptable device stability for future applications, which could be improved by using di-nuclear complexes [109,110]. However, examination of LECs characteristics revealed that this challenge could not overcome with Ru-19 and Ru-20 , the time for LECs to reach half of the initial luminance being of only 539 and 1104 s for Ru-19 and Ru-20 -based devices, respectively (See Figure 7 and Table 4) [111]. From this work, it can be, therefore, concluded that the design of polynuclear Ru-complexes requiring hard work from the synthetic point of view is useless and non-adapted for the design of long-living LECs.…”
Section: Metal Complexes Using Nir Emittersmentioning
confidence: 99%